Post-craniotomy Pain: An Update - Samagh, Navneh; Jangra, Kiran; Dey, Ankita (Journal of Neuroanaesthesiology and Critical Care, 2023)
Approximately two-thirds of patients experience moderate to severe intensity pain following craniotomy. It is often undertreated due to fear of unfavorable side effects of commonly used analgesic drugs. The objectives of this review are to discuss the various aspects of acute and chronic post-craniotomy pain including its incidence, pathophysiology, diagnostic criteria, preventive strategies, and management in adult patients. The data have been consolidated based on our literature search from 1978 to 2021 using various databases including Google Scholar, Medline, and PubMed Central. We conclude that one must act at the earliest using various treatment modalities for post-craniotomy pain management.
Keywords: acute post-craniotomy pain; chronic post-craniotomy pain; scalp bloc